Aplikasi Bahan Organik dan Mulsa pada Lahan Replanting Kelapa Sawit dengan Tanaman Hortikultura - Rima Purnamayani; Hery Nugroho; Yardha Yardha (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Oil palm Plantation at Muaro Jambi, Jambi province already aged over 25 years, so these plants are not productive anymore and needs to be rejuvenated. By doing rejuvenation means farmers will lose income while waiting for the palm oil crop production for 3-4 years. Intercrop between oil palm plantations have great resulted in improved land productivity, increase farmers' income as well as the main crop of palm maintained. Technological innovation between plants can be carried out on an oil palm plantation aged 1 to 3 years or before the plant produces. The aim is to optimize land use oil palm replanting with horticultural crops through the provision of organic matter and MPHP (Silver Black plastic mulch). The activities carried out in Mekarsari Makmur Village Muaro Jambi District. Horticultural crops that are cultivated eggplant, beans, bitter melon, squash and cucumber. The draft assessment used was a factorial randomized block design with two factors, namely: MPHP (MPHP Without and With MPHP) and the provision of organic material (Without organic fertilizers, Manure, Compost and manure + compost). For all commodities, the highest production was obtained at treatment MPHP use and manure, ie 20.9 tonnes of beans/ha, 8.99 tons of cucumbers/ha, 5.95 tons of squash/ha, 1.17 pare ton/ha and 6 , 8 tons of eggplant/ha